Potential and Characteristic of Biomass Pellet from Tea Plantation Wastes as Renewable Energy Alternative - Makbul Hajad; Sugeng Harianto; Joko Nugroho Wahyu Karyadi; Adhi Irianto Mastur; Muhammad Khais Prayoga; Heri Syahrian Khomaen; Elaine Faustine; Ivander Nainggolan; Fahmi Aryo Majid; Muhammad Hafidz Syahputra; Ganesha Afnan Adipradana (The University of Lampung, 2023)
Tea plantation biomass wastes, such as tea plantation pruning, shade trees, and woody weeds have not been utilized. The waste can be used as renewable energy in the form of wood pellets. The problem is the feasibility of biomass waste to be used as material for making wood pellets as energy. This paper aims to analyze the potential of tea plantation biomass waste as wood pellet material to meet energy needs. The research was conducted in a tea plantation owned by the Tea and Kina Research Center (PPTK). Quantification of biomass waste potential per unit area was conducted in the plantation using direct measurement method. Proximate analysis of each wood pellet variant of biomass waste was conducted to match the quality of Indonesian Wood Pellet Standard. The biomass waste potential in PPTK is 14,281 tons per year which can produce 8,186 tons of wood pellets per year. This potential can meet the needs of wood pellet consumption from the tea production process at PPTK which is around 1.8 tons / day for the tea processing process of 13 tons/day. Based on proximate analysis, the wood pellets produced have a calorific value of 4425 cal/gram, density of 1.35 grams/cm3, fixed carbon content of 85.2%, and volatile matter of 3.72%. These results confirm that the wood pellets comply with the National Wood Pellet Standard (SNI 8021:2014). This can be a model for the application of the Green Circular Economy concept in the plantation sector. Keywords: Biomass pellets; Green circular economy; Renewable energy; Tea plantation waste; Wood pellets